WATERSHED HYDROLOGICAL ANALYSIS OF JAKARTA EXTREME FLOODS - Anastasia Yunika Mukand Singh Babel Satoshi Takizawa (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2012)
Jakarta flood is a routine event. It occurs annually in rainy seasons while extreme flood takes place approximately every five years. Various factors, from natural to man-induced and technical to non-technical ones, are involved in causing the detrimental impacts of the flood. Among those factors, the existence of Ciliwung as the main river flowing across Jakarta leads to the complication of the problem. This study analyzed the main hydrologic parameters, i.e. rainfall and river discharge in Ciliwung’s catchment area, to assess the extreme floods in Jakarta. Three extreme flood events, i.e. two events in 1996 and one event in 2002 were analyzed based on the rainfall data at five stations overall area of Jakarta and river discharge at four stations along Ciliwung. The result of analysis revealed the factors of main causes of the extreme events. Furthermore, it is expected that by considering the past record of similar events in various study reports, precautions could be developed to anticipate predictable impacts from such events in the future, and recommendations could be provided as alternatives to overcome the problem.Keywords: discharge, flood, hydrological analysis, rainfall, watershed